Physical Pain, Opiate Prescription Medications, and Heroin Addiction: A Case Series. (December 2016) - Clements, David; Lopez, Juan C.; Rachakonda, Srivani; Sedky, Karim; Pumariega, Andres
Abstract : Objective: Opiate misuse epidemic and its associated morbidity and mortality have seen an alarming rise in the last decade. In recent years, the transition from prescription opiate misuse to heroin has also been noted. The aim of this review is to understand factors affecting the opiate epidemic and current deficits in the system to enhance management and improve outcomes for this population. Materials and Methods: Case presentation and literature review was conducted. Results: We present a case series that illustrates how medical and psychiatric disorders play a major role in the tragic transition many patients make from prescription analgesics to illicit heroin. Literature review suggests a strong relationship between decrease in the opiate prescription by physicians and the increase in heroin epidemic. Conclusions: Although preventive measures (ie, educating physicians and changing prescribing patterns) as well as enhancing treatments are being increased, more focus is needed to address management of addiction itself and its comorbidities (ie, psychiatric and medical disorders that increase risk of substance use).